ASOSIASI ANTARA ATTACHMENT STYLES DALAM HUBUNGAN ROMANTIS PADA RELATIONSHIP SATISFACTION (KEPUASAAN DALAM SUATU HUBUNGAN) - Wina Lova Riza (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2018)
This study aims to investigate the association between perceptions of childhood experiences with parents, attachment styles (avoidant, anxious/ambivalent, and security) in romantic relationships, and relationship satisfaction (satisfaction in relationships) with a sample of lecturers and employees of UBP in Karawang who have married or having a romantic relationship. The method used in this study is a regression method with the aim to find out the extent of the influence of one independent variable with the dependent variable. In other words, researchers intend to see the effect of variable attachment styles with relationship satisfaction. The research instrument used was to use two questionnaires with a Likert scale, namely the Experiences in Close Relationships-Revised (ECR-R) questionnaire and the relationship assessment scale. From the results of the study using multivariate correlation analysis with the SPSS 24 program, a significant value of 0.009 was obtained with a probability (p) of 0,000; because p <0.05, it indicates a significant relationship with a positive direction between attachment styles and relationship satisfaction. In addition, the following are the results of grouping the results of respondents' attachment style. From a total of 88 respondents, 50 of them (57%) have a fearful attachment style, 17 people (19%) have a dismissing attachment style, 11 people (13%) have a preocupied attachment style, and 10 (11%) have type of secure attachment style. Keywords: Attachment Styles, Relationship Satisfication, Romantic Relationship Penelitian ini bertujuan untuk menyelidiki asosiasi antara persepsi pengalaman masa kanak-kanak dengan orang tua, attachment styles (avoidant, anxious/ambivalent, dan security) dalam hubungan romantis, dan relationship satisfacation (kepuasaan dalam hubungan) dengan sampel dosen dan karyawan UBP Karawang yang telah menikah atau sedang menjalani hubungan romantis. Metode yang digunakan dalam penelitian ini adalah metode regresi dengan tujuan untuk mengetahui sejauh mana pengaruh satu variabel indenpenden dengan variabel dependen. Dengan kata lain, peneliti bermaksud untuk melihat pengaruh variabel attachment styles dengan relationship satisfaction. Instrumen penelitian yang digunakan adalah dengan menggunakan dua kuesioner dengan skala likert, yaitu kuesioner Experiences in Close Relationships-Revised (ECR-R) dan relationship assessment scale. Dari hasil penelitian dengan menggunakan analsis korelasi multivariat dengan program SPSS 24 diperoleh nilai signifikan sebesar 0,009 dengan probabilitas (p) 0,000; karena p < 0,05, maka menunjukkan adanya hubungan yang signifikan dengan arah positif antara attachment styles dengan relationship satisfaction. Sebagai tambahan, berikut dipaparkan hasil pengelompokkan hasil attachment style responden. Dari total 88 preponden, 50 orang diantaranya (57%) memiliki tipe fearful attachment style, 17 orang (19%) memiliki tipe dismissing attachment style, 11 orang (13%) memiliki tipe preocupied attachment style, dan 10 orang (11%) memiliki tipe secure attachment style. Kata Kunci: Attachment Styles, Relationship Satisfication, Romantic Relationship